Обеспечение отказоустойчивости решений по многоадресной маршрутизации в телекоммуникационной сети в условиях передачи мультипотокового трафика - Лемешко, О. В.; Арус, К. М.; Єременко, О. С. (My University, 2015)
Conditions for the node, link and path protection within the fault-tolerant routing for the multiflow case were proposed. Presented conditions are based on a nonlinear flow model which uses the terms for the links overload prevention modified for the case when just some of the flows switched to the backup paths, but not all of them.
Keywords: телекоммуникации; отказоустойчивость; маршрутизация; потоковая модель; схема резервирования; многоадресный поток